Preference of Santri in Increasing Interest of Saving at Sharia Banks in Malang Regency : Study at Islamic Boarding School of Annur Bululawang - Roisul Adib (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2021)
At present the sharia banking sector is experiencing relatively rapid growth. Islamic banking is able to show high acceleration of growth with an average growth of 40.20% per year in the last five years (2015-2020). While the average national banking growth was only 16.7%. Therefore, Islamic banking is nicknamed